The effect of litter decomposition mostly depends on seasonal variation of ultraviolet radiation rather than species in a hyper-arid desert - Wang, Peng; Liu, Yalan; Zhang, Bo; Li, Lei; Lin, Lisha; Li, Xiangyi; Zeng, Qiang (Frontiers in Environmental Science, 2024)
Ultraviolet (UV) radiation is believed to play a significant role in accelerating litter decomposition in water-limited ecosystems. Litter traits also influence the decomposition. However, the dominance of litter traits and ultraviolet radiation on litter decomposition in hyper-arid deserts (annual precipitation: potential evaporation < 0.05) with diverse species and seasonal variations remain unclear. To address this knowledge gap, we examined the decomposition of three dominant litter species (Karelinia caspia, Alhagi sparsifolia, and Populus euphratica) in the southern edge of the Taklimakan Desert, Northwest China. Our results revealed that under UV radiation conditions, K. caspia, A. sparsifolia, and P. euphratica experienced mass losses of 45.4%, 39.8%, and 34.9%, respectively, and 20%, 22.2% and 17.4%, respectively under UV filtering treatment. Specifically, the loss rate of carbon and lignin under UV radiation, was 2.5 and 2.2 times higher than under UV filtering treatment, respectively. Furthermore, UV radiation did not dominate decomposition throughout the year in our study area, and the loss rate of litter traits was significantly higher in summer than in winter under UV radiation. Moreover, this photodegradation is related to the intensity of UV exposure, but not to precipitation or temperature. Surprisingly, species type had no significant effect on litter decomposition. However, when we applied a UV filtering treatment, we observed higher loss rates of nitrogen compared with the ambient treatment, suggesting the involvement of other spectra in the litter decomposition process. Overall, our findings elucidate that UV radiation is a crucial factor that affects litter mass loss. The magnitude of this effect mostly varies with the season rather than the species of litter.